2013
DOI: 10.1214/12-aos1065
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of latent mixing measures in finite and infinite mixture models

Abstract: This paper studies convergence behavior of latent mixing measures that arise in finite and infinite mixture models, using transportation distances (i.e., Wasserstein metrics). The relationship between Wasserstein distances on the space of mixing measures and f -divergence functionals such as Hellinger and Kullback-Leibler distances on the space of mixture distributions is investigated in detail using various identifiability conditions. Convergence in Wasserstein metrics for discrete measures implies convergenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(187 citation statements)
references
References 41 publications
4
183
0
Order By: Relevance
“…implies G = G ′.) While Nguyen (2013) has shown that under certain conditions, DPMs are consistent for the mixing distribution (in the Wasserstein metric), Miller and Harrison (2013, 2014) have shown that the DPM posterior on the number of clusters is typically not consistent for the number of components, at least when the concentration parameter is fixed; the question remains open when using a prior on the concentration parameter, but we conjecture that it is still not consistent. On the other hand, MFMs are consistent for the mixing distribution and the number of components (for Lebesgue almost-all values of the true parameters) under very general conditions (Nobile, 1994); this is a straightforward consequence of Doob’s theorem.…”
Section: Empirical Demonstrationsmentioning
confidence: 99%
“…implies G = G ′.) While Nguyen (2013) has shown that under certain conditions, DPMs are consistent for the mixing distribution (in the Wasserstein metric), Miller and Harrison (2013, 2014) have shown that the DPM posterior on the number of clusters is typically not consistent for the number of components, at least when the concentration parameter is fixed; the question remains open when using a prior on the concentration parameter, but we conjecture that it is still not consistent. On the other hand, MFMs are consistent for the mixing distribution and the number of components (for Lebesgue almost-all values of the true parameters) under very general conditions (Nobile, 1994); this is a straightforward consequence of Doob’s theorem.…”
Section: Empirical Demonstrationsmentioning
confidence: 99%
“…Set ε = ε 1 , the conclusion then follows by invoking Equation (12). The scenario of (ii) proceeds in the same way.…”
Section: Theoremmentioning
confidence: 94%
“…This framework continues to be very useful, but the analysis of mixing measure estimation in multi-level models presents distinct new challenges. In Section 4, we shall formulate an abstract theorem (Theorem 4) on posterior contraction of latent variables of interest in an admixture model, given m × n data, by reposing on the framework of [7] (see also [12]). The main novelty here is that we work on the space of latent variables (e.g., space of latent population structures endowed with Hausdorff or a comparable metric) as opposed to the space of data densities endowed with Hellinger metric.…”
Section: Methods Of Proofs and Toolsmentioning
confidence: 99%
See 2 more Smart Citations